2006
DOI: 10.1063/1.2202704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid thermal annealing on device characteristics of InGaAs∕GaAs quantum dot infrared photodetectors

Abstract: In this work, rapid thermal annealing was performed on InGaAs∕GaAs quantum dot infrared photodetectors (QDIPs) at different temperatures. The photoluminescence showed a blueshifted spectrum in comparison with the as-grown sample when the annealing temperature was higher than 700°C, as a result of thermal interdiffusion of the quantum dots (QDs). Correspondingly, the spectral response from the annealed QDIP exhibited a redshift. At the higher annealing temperature of 800°C, in addition to the largely redshifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
2
23
1
Order By: Relevance
“…However, in-plane polarized radiation causing transition to well bound first excited state(s) can hardly cause a strong photocurrent response. On the other hand, the mid-infrared response has been observed on many occasions in experiments performed in normal--incidence geometry [7,28,29]. This would contradict the results previously mentioned if one assumed ideally in-plane polarized radiation in these experiments.…”
Section: Intraband Optical Propertiescontrasting
confidence: 52%
“…However, in-plane polarized radiation causing transition to well bound first excited state(s) can hardly cause a strong photocurrent response. On the other hand, the mid-infrared response has been observed on many occasions in experiments performed in normal--incidence geometry [7,28,29]. This would contradict the results previously mentioned if one assumed ideally in-plane polarized radiation in these experiments.…”
Section: Intraband Optical Propertiescontrasting
confidence: 52%
“…Inter-diffusion studies have been carried out on various QD structures by using the ion implantation [9] and dielectric capping [10,11] methods. Fu et al [12] ascribed a 1.3-mm shift in the spectral response from the asgrown value of 6.1 mm; however, a significant degradation of device performance was also observed. In another study, Aivaliotis et al [13] observed wide spectral tuning of InAs/In 0.15 Ga 0.85 As/ GaAs dot-in-a-well (DWELL) infrared photodetectors using postgrowth RTA, but the detectivity also decreased in the annealed QDIP.…”
Section: Introductionmentioning
confidence: 92%
“…Reduction in vertical dot spacing increases the dark current through intradot tunneling. Experiments on rapid thermal annealing of quantum dots have shown improved PL performance but degradation in the QDIP device performance due to strain relaxation [39,80,81] has been observed. Size variation in quantum dots can be reduced by using punctuated island growth [82].…”
Section: Epitaxial Growth and Device Designmentioning
confidence: 99%
“…After about a decade of research, QDIPs are beginning to outperform QWIPs by demonstrating lower dark current and higher operating temperature [30][31][32]. Various groups have been working on methods to improve the structural and optical properties of quantum dots [31,[33][34][35][36][37][38][39][40] to increase carrier lifetime as well as to increase quantum dot density. Dark current levels have been significantly reduced by using AlGaAs as current blocking layers [41][42][43].…”
Section: Introductionmentioning
confidence: 99%